The role of the gastronomic component in expressing the axiological meaning of Tuvan proverbs (against the background of Russian and French material) - Nelyubova, Natalia Yu.; Sknarev, Dmitry S.; Kol, Choduraa Sh. (The New Research of Tuva, 2024)
The article presents an axiological analysis of Tuvan proverbs and sayings with gastronomic themes, comparing them to Russian and French proverbs. The analysis is based on a card file of the author, which was compiled by continuously sampling from paremiographic sources in three languages. The sampling was done according to a thematic principle. The conducted research has revealed the significant role of food in the expression of axiological meanings in paroemias from three different languages. Identified symbols represent gastronomic traditions of different ethnic groups and allow us to identify both universal and unique features in the perception of values and specific life situations. For Tuvan paroemias, it is common to use names of various meats, dairy products, and grains, which are traditional food items that serve as a symbolic basis for expressing various values and value pairs, such as work — laziness, friendship — family, people — wealth, and beauty. In contrast, the Russian material shows a connection between gastronomic proverbs and various topics, but food is not seen as a value itself, but rather as a necessary part of life. The representation of food as a separate value is clearly expressed in French parodies, where a large number of different food components are revealed. Gastronomic traditions are an important part of French culture, and this is reflected in the language. The French dictionary has a separate section devoted to food and dining, which further emphasizes the importance of food in French culture. In contrast, the Tuvan and Russian languages do not have such a dedicated section for food. This difference in approach to food may be due to cultural differences between the three languages. However, food plays an important role in the French cultural code.